2013
DOI: 10.1590/s0103-84782013001100016
|View full text |Cite
|
Sign up to set email alerts
|

Proteinograma sérico e do líquido peritoneal de equinos hígidos e daqueles submetidos à obstrução intestinal experimental

Abstract: Avaliou-se a resposta de fase aguda através da concentração das proteínas de fase aguda (PFA) no soro sanguíneo e no líquido peritoneal de vinte e um equinos, hígidos e submetidos à obstrução intestinal experimental, distribuídos em quatro grupos: obstrução de duodeno - GD (n=6), íleo - GI (n=6), cólon dorsal esquerdo - GM (n=6) e controle instrumentado - GC (n=3). Foram colhidas amostras de sangue e líquido peritoneal e, após centrifugação e fracionamento, as proteínas de fase aguda foram separadas por eletro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
4
0
4
Order By: Relevance
“…Digestive diseases probably increased this APP in the PF of animals evaluated this study, particularly in intestinal obstructions, intussusceptions, and other diseases that affected the digestive system. In this sense, Nogueira et al (2013) confirmed that the evaluation of PF is more sensitive and effective in the diagnosis and monitoring of abdominal inflammatory processes in the equine species than the serum evaluation.…”
Section: Proteinogramsupporting
confidence: 54%
See 1 more Smart Citation
“…Digestive diseases probably increased this APP in the PF of animals evaluated this study, particularly in intestinal obstructions, intussusceptions, and other diseases that affected the digestive system. In this sense, Nogueira et al (2013) confirmed that the evaluation of PF is more sensitive and effective in the diagnosis and monitoring of abdominal inflammatory processes in the equine species than the serum evaluation.…”
Section: Proteinogramsupporting
confidence: 54%
“…Soares (2008) also reported an increase in transferrin concentration in PF in calves with the hernia. Nogueira et al (2010) and Nogueira, Di Filippo, Anai, Pereira and Santana(2013) also observed an increase in this APP in the PF of horses with experimental intestinal obstructions, which was attributed to an inflammatory lesion resulting from the surgical procedure and the enteric lesion, giving a positive APP behavior in PF.…”
Section: Proteinogrammentioning
confidence: 87%
“…No estro esta proteína correspondeu a aproximadamente 1,70% das proteínas séricas e no diestro a 1,45%. Há relatos de valores semelhantes àqueles encontrados neste estudo, reportados por Nogueira et al (2013).…”
Section: Resultsunclassified
“…Após o acasalamento da égua normalmente ocorre um processo inflamatório auto limitante, visando à remoção do excesso de espermatozoides, plasma seminal, debris e contaminantes uterinos (Samper et al, 2016). É essencial para o desenvolvimento do embrião que o endométrio uterino se mantenha hígido e isento de quaisquer alterações ambientais e contaminações (Panzani et al, 2014).…”
Section: Introductionunclassified
“…No Brasil, a importância da análise do LP no diagnóstico afecções abdominais de equinos e asininos também tem ganhado destaque. Nessa última década, estudos com líquido peritoneal de cavalos foram realizados e seus efeitos de processo obstrutivos (DI FILIPPO et al, 2009;DI FILIPPO et al, 2010;DI FILIPPO et al, 2012;NOGUEIRA et al, 2013, VIERA et al, 2018), parasitários (LLAMAS et al, 2015 e da castração em equinos (DI FILIPPO et al, 2014;DI FILIPPO et al, 2016) e asininos (BARROS et al, 2018).…”
Section: Introductionunclassified